As vontades de sentido e de potência: Viktor Frankl vai ao encontro de Friedrich Nietzsche. - Ferreira, Sérgio Gonçalves (2021)
The objective of this thesis was to verify whether the conception of the will to power, thought by Nietzsche, is in tune with the will to meaning, conceptualized by psychiatrist Viktor Frankl, the creator of logotherapy, or psychotherapy of the meaning of life. Additionally, we made an effort to verify if this conceptual relationship has as its guiding thread the will to meaning as a desire that runs through existence, from a basic will, to the conscious thought of ones´s desires. The research had as its starting point the observation that the psychiatrist, several times, cited the following thought by Nietzsche: "He who has a reason to live for can bear almost any how". Based on it, Frankl registred in his work: "I can see in these words a motto which holds true for any psychotherapy". The psychiatrist was a survivor of Nazi concentration camps and this fact gave him a deep understanding of suffering, a phenomenon that also interested the philosopher, a thinker concerned with the tragedy in human life. For a better understanding of this work, the following information is important: psychoanalysis is also known as the first Viennese school of psychotherapy; logotherapy as the third Viennese school of psychotherapy; and, in the middle of these two is the school of individual psychology, created by Alfred Adler. To understand the differences between schools, one aspect is highlighted: logotherapy works with three dimensions: body, mind and spirit (noological dimension), and it is through this third dimension that human beings question the meaning of life. In another aspect, both psychoanalysis and individual psychotherapy perceive only the first two dimensions in the human organism. The thesis was conducted as an exploratory study, which fundamentally used the bibliographic research method, mainly through reading the authors themselves. To accomplish the objective, the work was divided into three parts: initially, Nietzsche's reasonings were presented, which, according to the author of the thesis, deal with wanting to give meaning to life. The second part presents the theoretical concepts developed by Viktor Frankl, with research focused on his books in Portuguese, noting that it is enough to understand the fundamentals of logotherapy. The third block of the work cross-referenced the conceptions of the thinkers, and it is in this part, as well as in the conclusion, that the thesis sought to go further, in its own way, creating bridges between Nietzsche and Viktor Frankl.